Estratégia de fertirrigação no cultivo da alface (lactuca sativa l.) em substrato - Targino, Ana Jacqueline de Oliveira (2017)
The objective of this work was to evaluate different strategies of fertirrigation management for lettuce in substrate, with emphasis on the use of saline water in the preparation of the nutrient solution. The research was divided in four experiments, all with randomized block design, with three replicates of four plants. The first experiment evaluated different irrigation frequencies (6, 9 and 12 daily events) and pot volumes (0.5, 1.0 and 3.0 L), in a 3 x 3 factorial scheme. In the second experiment, a 2 x 3 x 3 factorial scheme was employed, which evaluated two water salinity levels (0.5 and 2.0 dS m-1), three irrigation frequencies (6, 9 and 12 daily events) and three pot volumes (0.5 , 1.0 and 3.0 L). In the third experiment, was evaluated the effect of four combinations of N / K / Ca (F1 = 1: 1: 1, F2 = 1.5: 1: 1, F3 = 1: 1.5: 1, F4 = 1: 1: 1.5), with two irrigation water salinity levels (0.5 and 2.0 dS m-1), and two pot volumes (1.0 and 3.0 L), composing a 4 x 2 x 2 factorial scheme. In the fourth experiment, five nutritive solutions with different levels of K (S1, S2, S3, S4 and S5) and two pot volumes (1 and 3 L) were tested in a 5 x 2 factorial scheme. At the end of each experiment, plants were collected and the following variables were evaluated: stem diameter, total number of leaves, and number of commercial leaves, leaf area, total fresh mass, total dry mass, leaf succulence, specific leaf area and water content of leaves. The data were submitted to analysis of variance, means were compared by the Tukey test (5%), and the factors were split whenever there was a significant response of the interaction between them. In general, it was observed that the lettuce presents good production in pots of 1.0 L, independently of the salinity of irrigation water. The frequency of 9 daily events was sufficient for lettuce production. The use of higher concentrations of nitrogen in the fertigation (F4) provided a reduction in the rates of deleterious effects caused by the salinity of the irrigation water. As well as, the addition of 50% of the potassium values (S4) in standard fertigation is more favorable to lettuce irrigation with water of higher saline level